Pernikahan Dini di Kalangan Remaja SMP Kota Kabanjahe - Andriani, Anisah; Jailani, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Early marriage in Indonesia, especially in Kabanjahe, is a complex social issue that still occurs with high frequency. This study aims to identify the factors that cause early marriage among junior high school students and evaluate the prevention efforts made by the school. The method used was qualitative with a descriptive approach, involving in-depth interviews with perpetrators of early marriage, teachers, and other related parties. The results showed that economic factors, low education, and cultural and social pressures are the main drivers of early marriage. In addition, the impact of the COVID-19 pandemic has exacerbated this situation with an increase in the number of marriage dispensations. This study recommends the need for collaboration between schools, families and communities in prevention efforts, as well as the importance of comprehensive education on the risks of early marriage. It is hoped that the results of this study can serve as a reference in developing more effective policies to protect children from early marriage practices.